Happy High-performing Managers - Hosie, Peter; Sevastos, Peter; Travaglione, Tony (Australian Academic Press, 2007)
There has long been an adherence to the intuitively appealing notion that happy employees perform better. But decades of research have been unable to establish a strong link between job satisfaction and performance. In large part, this has resulted from researchers erroneously conceiving an operationalising job satisfaction as being identical to affective wellbeing. Belief in the 'happy-productive worker' thesis has its roots in the human behaviour school of the 1950s. Similarly, the 1970s human relations movement had a significant influence on job redesign and quality-of-life initiatives and was credited with specifying the original satisfaction-performance relationship (Strauss, 1968). Despite mixed empirical evidence, there is support in the literature to suggest that a relationship exists between manager's affective wellbeing, intrinsic job satisfaction and their performance.This study investigated the relationship between manager's job-related affective wellbeing ('affective wellbeing'), intrinsic job satisfaction and their contextual and task job performance ('managers' performance'). Specifically, the main goal was to establish which indicators o manager's affective well being and intrinsic job satisfaction might predict dimensions of their' contextual and task performance.